Politics, Cinema and Music in Brazil and Spain from the 30s (Global Journal of Human-Social Science, 2024)
This article sets out to make a comparative analysis of the cinema during the 1930s in Brazil and Spain taking into account the political factors that influenced directly or indirectly in the artistic and cultural context of these two countries To achieve this goal a bibliographical survey of the history of cinema in Brazil and Spain was made as well as the comparison of the quantity and circumstances in which many films were produced focusing also on their relationship with other artistic sectors The results point to an important contribution of music to the formation of a national film genre presenting itself as a responsible element for a more national and more structured cinematographic production in both countries
Keywords: cinema; music; Brazil; Spain